2019
DOI: 10.1016/j.celrep.2019.04.091
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Antibodies Targeting the CD39/CD73 Immunosuppressive Pathway Unleash Immune Responses in Combination Cancer Therapies

Abstract: Highlights d IPH5201 and IPH5301 block cell-borne and soluble CD39 and CD73, respectively d IPH5201 maintains immunogenic extracellular ATP d When used in combination with chemotherapy, IPH5201 promotes antitumor immunity d Targeting CD39 and CD73 synergistically promotes cancer patient T cell activation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
290
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 323 publications
(301 citation statements)
references
References 49 publications
7
290
2
2
Order By: Relevance
“…CD39 and CD73 can participate in an immunosuppressive pathway that leads to the degradation of the (immunostimulatory) pool of extracellular ATP to the immunosuppressive metabolite adenosine. Indeed, pharmacological inhibitors targeting CD39, CD73, or adenosinergic receptors are being developed for immunostimulation, exemplifying yet another strategy for the metabolic intervention on cancer. However, it is also known that some facets of immunosurveillance (and in particular T cell expansion) may rely on OXPHOS .…”
Section: Conclusion Limitations and Perspectivesmentioning
confidence: 99%
“…CD39 and CD73 can participate in an immunosuppressive pathway that leads to the degradation of the (immunostimulatory) pool of extracellular ATP to the immunosuppressive metabolite adenosine. Indeed, pharmacological inhibitors targeting CD39, CD73, or adenosinergic receptors are being developed for immunostimulation, exemplifying yet another strategy for the metabolic intervention on cancer. However, it is also known that some facets of immunosurveillance (and in particular T cell expansion) may rely on OXPHOS .…”
Section: Conclusion Limitations and Perspectivesmentioning
confidence: 99%
“…In the hypoxic TME, NAD+ is produced by the salvage pathway and is metabolized by ectoenzymes to form adenosine, a nucleoside that regulates the immune response. In hypoxic conditions, adenosine suppresses the anti-tumor immune response by recruiting myeloid-derived suppressor cells and T regulatory cells, which inhibits the activity of T effector cells and thus favors tumor progression [18,19]. CD38 is one of the three ectoenzymes involved in the production of adenosine through the CD38/CD203a/CD73 adenosinergic pathway.…”
Section: The Role Of Cd38 In the Tmementioning
confidence: 99%
“…This inhibits both the innate and the adaptive immune response, and results in an immunosuppressive TME. Adenosine further suppresses the anti-tumor immune response under hypoxic conditions by recruiting myeloid-derived suppressor cells and T regulatory cells, further inhibiting the activity of T effector cells and favoring tumor progression [18,19]. Previous studies have shown that immunosuppression in the TME can be reduced by inhibiting either the enzymes or receptors in the adenosinergic pathway.…”
Section: The Role Of Cd38 In the Tmementioning
confidence: 99%
“…In the last few years, exciting progress has been made in the development of immunotherapy for the treatment of cancer patients. Modulation of the immune system through a small‐molecule approach offers several unique advantages (e.g., lower cost and ease of administration) that are complementary to and potentially synergistic with immuno‐oncology approaches using monoclonal antibodies . This is exemplified by the association of two monoclonal antibodies (mAbs), one targeting CD73 (MEDI‐9447) and one neutralizing the immune check point PD‐1.…”
Section: Introductionmentioning
confidence: 99%